2005
DOI: 10.2136/sssaj2004.0332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Air and Water Permeability between Disturbed and Undisturbed Soils

Abstract: Although soil structure and pore geometry characteristics largely control flow and transport processes in soils, there is a general lack of experiments that study the effects of soil structure and pore‐space characteristics on air and water permeability. Our objective was to determine the dependency of soil permeability on fluid content for both water and air, and compare results for both disturbed (D) and undisturbed (UD) soils. For that purpose, we first measured the water permeability (kw) and air permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 30 publications
11
83
0
6
Order By: Relevance
“…Mohawesh et al (2005) showed that the saturated water content decreased with the increase in bulk density, and as a result the inflection point on the retention curve shifted to a lower matric potential. Tuli et al (2005) reported that the air and water permeabilities of undisturbed soil samples were significantly higher than those of disturbed samples, attributed to the changes of soil structure and macropores. Owing to high surface area and porosity of biochar, its addition to soils should influence soil structure and porosity through changing the bulk surface area, pore size distribution, and soil bulk density (Downie et al, 2009;Major et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mohawesh et al (2005) showed that the saturated water content decreased with the increase in bulk density, and as a result the inflection point on the retention curve shifted to a lower matric potential. Tuli et al (2005) reported that the air and water permeabilities of undisturbed soil samples were significantly higher than those of disturbed samples, attributed to the changes of soil structure and macropores. Owing to high surface area and porosity of biochar, its addition to soils should influence soil structure and porosity through changing the bulk surface area, pore size distribution, and soil bulk density (Downie et al, 2009;Major et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fine-textured clayey soils are of high fertility but often have a low hydraulic conductivity (Forsburg, 2003;Tuli et al, 2005). The infiltration of water into these soils is too slow therefore frequent surface ponding occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos têm definido a K a como dependente da estrutura do solo (IVERSEN et al, 2001;TULI et al, 2005;SILVA et al, 2009), influenciada pela Pt, distribuição e geometria do sistema poroso, tortuosidade, conectividade e constrição (MOLDRUP et al, 2003;DORNER;. Mais precisamente, a K a é condicionada em relação ao tamanho e continuidade dos Ma, considerados até mesmo mais importantes do que a quantidade de poros na determinação do fluxo de ar (BALL et al, 1988) e, portanto, sendo comum apresentar-se elevada nas camadas mais superficiais.…”
Section: Discussionunclassified
“…Esse resultado corrobora os de Silva et al (2009), os quais consideram que a K a depende Impacto do florestamento com Pinus taeda... basicamente do conteúdo de água e da densidade do solo, pois ambos influenciam a geometria e a continuidade do sistema poroso. Além disso, esse comportamento vem acompanhado da redução do carbono orgânico total, não favorecendo a estruturação e agregação do solo e, assim, influenciando a redução da aeração (TULI et al, 2005).…”
Section: Discussionunclassified